Characteristics of Banana Stem Adsorbent (Musa Paradisiaca) For Biogas Purification With Variation of Adsorption Contact Time - Elida Purba; Ferina Safitri (Jurnal Bahan Alam Terbarukan, 2023)
The features of the adsorbent utilized for biogas purification are covered in this study. The aim of this study was to investigate the features of the banana stem adsorbent that may be applied to the adsorption process for the purification of biogas. The research involved the preparation of banana stem powder, the removal of lignin, the creation of adsorbents, and the purification of biogas using the adsorption technique. The adsorption contact time variations used were (30; 60; 90) minutes, with a biogas flow rate of 1 l/minute and a banana stem particle size of 20 mesh. Samples were analyzed by lignocellulosic content analysis, FTIR (Fourier Transform Infrared Spectroscopy), SEM (Scanning Electron Microscope), and Gas Chromatography. According to the research findings, the adsorbent made from banana stems that can be used to purify biogas has a cellulose content of 47.5%, in the FT-IR analysis there is a shift in the peak number of stretching in the hydroxyl and carboxylic acid functional groups and has a surface structure of banana stem fiber that is orderly. The longer the contact time in the biogas purification process utilizing banana stem adsorbent with variations in adsorption contact time acquired, the more CO2 was adsorbed and the higher the CH4 concentration in the purified biogas. The biogas purification process resulted in a 39.893% reduction in CO2 content and the best contact time to produce the largest CH4 content was 90 minutes with the resulting CH4 content of 64.786%.